Anti-aging antiskid asphalt concrete and production process thereof

By integrating composite microspheres and fibers with specific structures into the asphalt concrete production, the asphalt's anti-aging and anti-skid performance is enhanced, addressing the decay issues and ensuring long-term durability and effectiveness.

CN119191761APending Publication Date: 2024-12-27LAISHUI DECHANG ASPHALT CONCRETE MFG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411160252.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Asphalt concrete pavements suffer from insufficient long-term anti-aging and anti-skid performance due to the rapid decay of anti-aging materials and anti-skid fillers under traffic loads and environmental factors, leading to cracking, rutting, and maintenance challenges.

Method used

Incorporating composite microspheres and fibers into the asphalt concrete production process, where composite microspheres are prepared with hollow mesoporous titanium oxide loaded with an asphalt regeneration agent and porphyrin structure, and composite fibers are based on basalt fiber with a cross-linked network formed by hyperbranched silane, enhancing heat and UV resistance and anti-skid properties.

Benefits of technology

The composite microspheres and fibers improve the asphalt concrete's long-term anti-aging and anti-skid performance by maintaining good quality and preventing degradation through slow release of the asphalt regeneration agent and forming a robust cross-linked network.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005006218880000121
    Figure BDA0005006218880000121
  • Figure BDA0005006218880000131
    Figure BDA0005006218880000131
Patent Text Reader

Abstract

The invention relates to the field of asphalt concrete, in particular to anti-aging and anti-skid asphalt concrete and a production process thereof.The anti-aging and anti-skid asphalt concrete is prepared from, by weight, 10-15 parts of matrix asphalt, 25-30 parts of coarse aggregate, 20-25 parts of fine aggregate, 20-30 parts of steel slag, 3-4 parts of butadiene styrene rubber, 6-8 parts of composite microspheres, 12-15 parts of composite fibers and 0.5-0.8 part of cross-linking agent; the composite microspheres are added into the asphalt concrete, so that the problem of insufficient long-term anti-aging performance of the existing asphalt concrete is solved, and the composite fibers are added, so that the defects of the performance of the asphalt concrete are overcome, and the use performance and quality of the asphalt concrete ground are improved. And therefore, good anti-skid performance can still be kept after long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of asphalt concrete, and in particular to an anti-aging and anti-skid asphalt concrete and a production process thereof. Background Art

[0002] With the continuous increase in traffic volume and traffic load, modern traffic has higher and higher performance requirements for asphalt concrete pavements. However, asphalt concrete pavements are affected by natural factors such as heat, oxygen, light and rain, resulting in aging, which makes them hard and brittle, and causes cracking, looseness and other defects, which seriously restricts the service life of asphalt pavements. In order to improve the anti-aging performance of asphalt concrete, anti-aging materials are usually added to asphalt to delay the aging of asphalt. However, the current anti-aging materials generally have problems such as short action time and material failure, which cannot meet market demand. At present, most asphalt concrete floors will choose to add steel slag as anti-skid filler to combine various types of aggregates to improve the anti-skid performance. However, with the effect of vehicle load and the polishing and wear of wheels, the anti-skid performance decays quickly, and even some roads have a large number of cracks, rutting, potholes and other defects. The maintenance department needs to invest a lot of money for repair and maintenance, which leads to a significant decline in the performance of asphalt concrete floors after a period of use, which cannot meet the anti-skid requirements. Summary of the invention

[0003] The purpose of the present invention is to provide an anti-aging and anti-skid asphalt concrete and its production process. By adding composite microspheres into the asphalt concrete, the problem of insufficient long-term anti-aging performance of the existing asphalt concrete is solved. By adding composite fibers, the insufficient performance of the asphalt concrete is supplemented, thereby improving the performance and quality of the asphalt concrete floor, thereby ensuring that it can still maintain good anti-skid performance after long-term use.

[0004] The purpose of the present invention can be achieved by the following technical scheme: A production process of anti-aging and anti-skid asphalt concrete, comprising the following steps: Step S1: weigh the following raw materials in parts by weight: 10-15 parts of matrix asphalt, 25-30 parts of coarse aggregate, 20-25 parts of fine aggregate, 20-30 parts of steel slag, 3-4 parts of styrene-butadiene rubber, 6-8 parts of composite microspheres, 12-15 parts of composite fibers and 0.5-0.8 parts of cross-linking agent;

[0005] Step S2: heating the base asphalt to 180° C., stirring and adding a mixture of coarse aggregate, fine aggregate and steel slag at a stirring rate of 400 rpm, stirring for 2-3 hours, then adding styrene-butadiene rubber, composite microspheres, composite fibers and a cross-linking agent, and continuing to stir for 2-3 hours to obtain an anti-aging and anti-skid asphalt concrete;

[0006] The composite microspheres are prepared by the following steps:

[0007] Step A1: mix hexadecyltrimethylammonium bromide, tetrabutyl titanate and anhydrous ethanol, stir and add deionized water at a stirring rate of 250-300rpm and room temperature, stir for 2-3h, heat to 120°C, react for 4-5h, centrifuge, dry, grind, and calcine at 500°C for 4h to obtain mesoporous titanium oxide, mix asphalt regeneration agent and anhydrous ethanol, stir and add mesoporous titanium oxide at a stirring rate of 400-450rpm and a temperature of 100°C, evacuate to 0.1MPa, and stir for 1h to obtain loaded titanium oxide;

[0008] The dosage ratio of hexadecyltrimethylammonium bromide, tetrabutyl titanate, anhydrous ethanol and deionized water is 2.8-3g:8-10g:40-50mL:8-10mL, and the dosage ratio of asphalt regeneration agent and mesoporous titanium oxide is 3-4g:0.6-0.8g;

[0009] During the reaction, mesoporous titanium oxide is prepared by a hydrothermal method using hexadecyltrimethylammonium bromide as a template and tetrabutyl titanate as a titanium source, and then the asphalt regeneration agent is loaded in the mesoporous titanium oxide by a vacuum loading method to obtain loaded titanium oxide;

[0010] Step A2: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and dichloromethane were mixed, and triethylamine and bis(trichloromethyl) carbonate were added under stirring at a rate of 120-150 rpm and room temperature, and the mixture was reacted for 10-15 minutes to obtain intermediate 1;

[0011] The ratio of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, triethylamine and bis(trichloromethyl) carbonate is 0.1-0.12 mol: 0.6-0.7 mol: 0.15-0.18 mol;

[0012] During the reaction, under the action of triethylamine and bis(trichloromethyl)carbonate, the amino group in 5,10,15,20-tetrakis(4-aminophenyl)porphyrin was isocyanated to obtain an intermediate 1 containing an isocyanate group;

[0013] Step A3: The loaded titanium oxide and 1,4-dioxane are mixed and ultrasonically dispersed for 10-15 minutes, and 5-sulfosalicylic acid is added under stirring at a rate of 120-140 rpm and a temperature of 80° C., and the mixture is reacted for 2-2.5 hours, and then the intermediate 1 is added and the temperature is lowered to 60° C., and the reaction is continued for 2-3 hours to obtain composite microspheres;

[0014] The ratio of supported titanium oxide, 5-sulfosalicylic acid and intermediate 1 is 0.6-0.8 g: 0.3-0.4 g: 0.02-0.03 mol;

[0015] During the reaction, the hydroxyl groups on the surface of the supported titanium oxide first react with the sulfonyl groups in 5-sulfosalicylic acid to form sulfonate groups, thereby fixing the 5-sulfosalicylic acid on the surface of the supported titanium oxide, and then the intermediate 1 is added, and the isocyanate groups in the intermediate 1 react with the hydroxyl groups in the 5-sulfosalicylic acid, thereby introducing isocyanate groups and porphyrin structures to prepare composite microspheres;

[0016] The composite fiber is prepared by the following steps:

[0017] Step B1: Graphene oxide, caprolactam and deionized water were mixed, stirred at a stirring rate of 80-100 rpm and a temperature of 80° C. for 15 min, then ultrasonically dispersed for 30 min, stirred and magnesium chloride hexahydrate was added, and the stirring was continued for 2 h, and the mixture was distilled under reduced pressure, and then the temperature was raised to 100° C. and sodium hydroxide was added, and the reaction was carried out for 2-3 h to obtain a precursor 1;

[0018] The amount ratio of graphene oxide, caprolactam, deionized water, magnesium chloride hexahydrate and sodium hydroxide is 0.5-0.6g:95-100g:50-60mL:3-3.5g:1.2-1.5g;

[0019] In the reaction process, caprolactam is used as a solvent, magnesium chloride hexahydrate and sodium hydroxide are used as raw materials, and graphene oxide is used as a carrier. Through a chemical precipitation method, magnesium chloride hexahydrate and sodium hydroxide react to generate magnesium hydroxide and load it on graphene oxide to obtain a precursor 1.

[0020] Step B2: Tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol are mixed, and the mixture is reacted for 12 hours at a stirring rate of 120-150 rpm and a temperature of 80° C. to obtain an intermediate a; the intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid are mixed, and the mixture is reacted for 3-4 hours at a stirring rate of 60-80 rpm and a temperature of 140° C. under nitrogen protection to obtain a hyperbranched siloxane;

[0021] The ratio of tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol is 0.03-0.032 mol: 0.03-0.032 mol: 50-60 mL, and the ratio of intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid is 0.01-0.012 mol: 5-6 g: 0.04-0.05 g;

[0022] During the reaction, the amino group in trishydroxymethylaminomethane reacts with the anhydride group in maleic anhydride to obtain an intermediate a containing a double bond. Since the intermediate a contains a carboxyl group and a hydroxyl group, under the action of p-toluenesulfonic acid, the intermediate a undergoes an esterification reaction by itself and simultaneously undergoes an esterification reaction with the hydroxyl group in the hydroxyl-terminated polysiloxane, thereby forming a hyperbranched siloxane with terminal hydroxyl groups.

[0023] Step B3: Precursor 1, hyperbranched siloxane and N,N-dimethylformamide are mixed and ultrasonically dispersed for 30 minutes, and reacted for 24 hours at a stirring rate of 150-180 rpm and a temperature of 130°C to obtain precursor 2, 3-mercaptopropyltriethoxysilane and ethanol solution are mixed, and basalt fiber is added at a stirring rate of 100-120 rpm and room temperature, and reacted for 2-3 hours, and then precursor 2 is added, and the reaction is continued for 4-6 hours to obtain composite fibers;

[0024] The amount ratio of precursor 1, hyperbranched siloxane and N,N-dimethylformamide is 1.2-1.4g: 3-4g: 80-100mL, the mass fraction of the ethanol solution is 70%, and the amount ratio of 3-mercaptopropyltriethoxysilane, ethanol solution, basalt fiber and precursor 2 is 8-10g: 1000mL: 15-20g: 3-4g;

[0025] During the reaction, since graphene oxide in precursor 1 contains a large number of carboxyl groups, it undergoes an esterification reaction with the terminal hydroxyl groups in the hyperbranched siloxane to obtain precursor 2, and 3-mercaptopropyltriethoxysilane is hydrolyzed in an ethanol solution and grafted onto the basalt fiber, thereby introducing mercapto groups, which then undergo a click reaction with the unsaturated double bonds in precursor 2 to obtain composite fibers.

[0026] Beneficial effects of the invention: The invention discloses an anti-aging and anti-skid asphalt concrete and its production process. The problem of insufficient long-term anti-aging performance of the existing asphalt concrete is solved by adding composite microspheres into the asphalt concrete, and the insufficiency of the performance of the asphalt concrete is supplemented by adding composite fibers, thereby improving the performance and quality of the asphalt concrete floor, thereby ensuring that it can still maintain good anti-skid performance after long-term use; the composite microspheres are prepared by using hollow mesoporous titanium oxide as a matrix loaded with an asphalt regeneration agent, and at the same time compounding an intermediate a with 5-sulfosalicylic acid. Since the intermediate a contains a porphyrin structure, this structure can sensitize titanium oxide, thereby improving the light absorption performance of titanium oxide, thereby improving the anti-light aging performance of the asphalt concrete, and since the intermediate a contains unreacted isocyanate groups, the isocyanate groups can react with the matrix asphalt in the asphalt concrete, thereby forming a cross-linked network with the composite microspheres as nodes, thereby improving the heat aging resistance of the asphalt concrete, and since the composite microspheres The balls are loaded with asphalt regeneration agent, and have a hollow mesoporous structure. During long-term use, as water enters and interacts with alkaline substances in asphalt concrete, the grafts on the surface of the composite microspheres gradually unfold, thereby slowly releasing the asphalt regeneration agent, so that the asphalt concrete exhibits long-term anti-aging properties. The composite fiber is based on basalt fiber and is prepared by reaction grafting with hyperbranched silane and precursor 1. Since precursor 1 is based on graphene oxide as a carrier, magnesium hydroxide is generated by chemical precipitation and loaded on graphene oxide. The formed magnesium hydroxide and graphene oxide present a lamellar structure, and the lamellar structure avoids the degradation of basalt fiber during use. Magnesium hydroxide can be bonded with polar groups in the matrix asphalt. At the same time, the hyperbranched siloxane in the composite fiber contains a large number of hydroxyl groups, which react with the cross-linking agent to construct a cross-linking network in the asphalt concrete, thereby exerting the excellent performance of the composite fiber, ensuring that the asphalt concrete can still maintain good performance and quality after long-term use, thereby exhibiting good anti-slip properties. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1 A production process of anti-aging and anti-skid asphalt concrete comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 10 parts of commercially available Karamay Grade A matrix asphalt, 25 parts of commercially available Xiang'antong coarse aggregate, 25 parts of commercially available Yanhu fine aggregate, 20 parts of commercially available Yandong Haotian steel slag, 3 parts of commercially available Yunxin styrene-butadiene rubber, 6 parts of composite microspheres, 12 parts of composite fibers and 0.5 parts of tetraethoxysilane crosslinking agent;

[0029] Step S2: heating the base asphalt to 180° C., stirring and adding a mixture of coarse aggregate, fine aggregate and steel slag at a stirring rate of 400 rpm, stirring for 2 hours, then adding styrene-butadiene rubber, composite microspheres, composite fibers and a cross-linking agent, and continuing to stir for 3 hours to obtain an anti-aging and anti-skid asphalt concrete;

[0030] The composite microspheres are prepared by the following steps:

[0031] Step A1: mix hexadecyltrimethylammonium bromide, tetrabutyl titanate and anhydrous ethanol, stir and add deionized water at a stirring rate of 250 rpm and room temperature, stir for 2 hours, heat to 120°C, react for 4 hours, centrifuge, dry, grind, and calcine at 500°C for 4 hours to obtain mesoporous titanium oxide, mix commercially available Jixin Yibang asphalt regeneration agent and anhydrous ethanol, stir and add mesoporous titanium oxide at a stirring rate of 400 rpm and a temperature of 100°C, evacuate to 0.1 MPa, and stir for 1 hour to obtain loaded titanium oxide;

[0032] The dosage ratio of hexadecyltrimethylammonium bromide, tetrabutyl titanate, anhydrous ethanol and deionized water is 2.8g:8g:40mL:8mL, and the dosage ratio of asphalt regeneration agent and mesoporous titanium oxide is 3g:0.6g;

[0033] Step A2: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and dichloromethane were mixed, and triethylamine and bis(trichloromethyl) carbonate were added under stirring at a stirring rate of 120 rpm and room temperature, and the mixture was reacted for 10 min to obtain intermediate 1;

[0034] The ratio of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, triethylamine and bis(trichloromethyl) carbonate is 0.1 mol:0.6 mol:0.15 mol;

[0035] Step A3: The loaded titanium oxide and 1,4-dioxane were mixed and ultrasonically dispersed for 10 minutes, and 5-sulfosalicylic acid was added under stirring at a rate of 120 rpm and a temperature of 80°C, and the mixture was reacted for 2 hours. Then, the intermediate 1 was added and the temperature was lowered to 60°C, and the reaction was continued for 2 hours to obtain composite microspheres;

[0036] The ratio of supported titanium oxide, 5-sulfosalicylic acid and intermediate 1 is 0.6 g: 0.3 g: 0.02 mol;

[0037] The composite fiber is prepared by the following steps:

[0038] Step B1: commercially available Xinyuhong graphene oxide, caprolactam and deionized water were mixed, stirred at a stirring rate of 80 rpm and a temperature of 80°C for 15 min, then ultrasonically dispersed for 30 min, stirred and magnesium chloride hexahydrate was added, and the stirring was continued for 2 h, and the mixture was distilled under reduced pressure, and then the temperature was raised to 100°C and sodium hydroxide was added, and the reaction was carried out for 2 h to obtain a precursor 1;

[0039] The amount ratio of graphene oxide, caprolactam, deionized water, magnesium chloride hexahydrate and sodium hydroxide is 0.5g:95g:50mL:3g:1.2g;

[0040] Step B2: Tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol were mixed, and the mixture was reacted for 12 hours at a stirring rate of 120 rpm and a temperature of 80° C. to obtain intermediate a; intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid were mixed, and the mixture was reacted for 3 hours at a stirring rate of 60 rpm and a temperature of 140° C. under nitrogen protection to obtain hyperbranched siloxane;

[0041] The ratio of tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol is 0.03 mol: 0.03 mol: 500 mL, and the ratio of intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid is 0.01 mol: 5 g: 0.04 g;

[0042] Step B3: Precursor 1, hyperbranched siloxane and N,N-dimethylformamide were mixed and ultrasonically dispersed for 30 minutes, and reacted for 24 hours at a stirring rate of 150 rpm and a temperature of 130°C to obtain precursor 2, 3-mercaptopropyltriethoxysilane and ethanol solution were mixed, and stirred at a stirring rate of 100 rpm and room temperature, and commercially available Taicheng basalt fiber was added and reacted for 2 hours, and then precursor 2 was added and the reaction was continued for 4 hours to obtain composite fibers;

[0043] The amount ratio of precursor 1, hyperbranched siloxane and N,N-dimethylformamide is 1.2g:3-4g:80mL, the mass fraction of the ethanol solution is 70%, and the amount ratio of 3-mercaptopropyltriethoxysilane, ethanol solution, basalt fiber and precursor 2 is 8g:1000mL:15g:3g.

[0044] Embodiment 2 A production process of anti-aging and anti-skid asphalt concrete comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 15 parts of commercially available Karamay Grade A matrix asphalt, 25 parts of commercially available Xiang'antong coarse aggregate, 25 parts of commercially available Yanhu fine aggregate, 20 parts of commercially available Yandong Haotian steel slag, 4 parts of commercially available Yunxin styrene-butadiene rubber, 8 parts of composite microspheres, 12 parts of composite fibers and 0.8 parts of tetraethoxysilane crosslinking agent;

[0045] Step S2: heating the base asphalt to 180° C., stirring and adding a mixture of coarse aggregate, fine aggregate and steel slag at a stirring rate of 400 rpm, stirring for 3 hours, then adding styrene-butadiene rubber, composite microspheres, composite fibers and a cross-linking agent, and continuing to stir for 2 hours to obtain an anti-aging and anti-skid asphalt concrete;

[0046] The composite microspheres are prepared by the following steps:

[0047] Step A1: mix hexadecyltrimethylammonium bromide, tetrabutyl titanate and anhydrous ethanol, stir and add deionized water at a stirring rate of 300 rpm and room temperature, stir for 2 hours, heat to 120°C, react for 5 hours, centrifuge, dry, grind, and calcine at 500°C for 4 hours to obtain mesoporous titanium oxide, mix commercially available Jixin Yibang asphalt regeneration agent and anhydrous ethanol, stir and add mesoporous titanium oxide at a stirring rate of 450 rpm and a temperature of 100°C, evacuate to 0.1 MPa, and stir for 1 hour to obtain loaded titanium oxide;

[0048] The dosage ratio of hexadecyltrimethylammonium bromide, tetrabutyl titanate, anhydrous ethanol and deionized water is 3g:10g:40mL:10mL, and the dosage ratio of asphalt regeneration agent and mesoporous titanium oxide is 3g:0.8g;

[0049] Step A2: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and dichloromethane were mixed, and triethylamine and bis(trichloromethyl) carbonate were added under stirring at a stirring rate of 120 rpm and room temperature, and the mixture was reacted for 15 min to obtain intermediate 1;

[0050] The ratio of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, triethylamine and bis(trichloromethyl) carbonate is 0.12 mol:0.6 mol:0.18 mol;

[0051] Step A3: The loaded titanium oxide and 1,4-dioxane were mixed and ultrasonically dispersed for 15 minutes, and 5-sulfosalicylic acid was added under stirring at a rate of 120 rpm and a temperature of 80°C, and the mixture was reacted for 2.5 hours. Then, the intermediate 1 was added and the temperature was lowered to 60°C, and the reaction was continued for 2 hours to obtain composite microspheres;

[0052] The ratio of supported titanium oxide, 5-sulfosalicylic acid and intermediate 1 is 0.8 g: 0.3 g: 0.03 mol;

[0053] The composite fiber is prepared by the following steps:

[0054] Step B1: Mix commercially available Xinyuhong graphene oxide, caprolactam and deionized water, stir for 15 min at a stirring rate of 80 rpm and a temperature of 80°C, then ultrasonically disperse for 30 min, stir and add magnesium chloride hexahydrate, continue stirring for 2 h, distill under reduced pressure, then heat to 100°C and add sodium hydroxide, react for 2-3 h, and obtain precursor 1;

[0055] The amount ratio of graphene oxide, caprolactam, deionized water, magnesium chloride hexahydrate and sodium hydroxide is 0.6g:100g:50mL:3g:1.5g;

[0056] Step B2: Tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol were mixed, and the mixture was reacted for 12 hours at a stirring rate of 120 rpm and a temperature of 80° C. to obtain intermediate a; intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid were mixed, and the mixture was reacted for 3 hours at a stirring rate of 80 rpm and a temperature of 140° C. under nitrogen protection to obtain hyperbranched siloxane;

[0057] The ratio of tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol is 0.032 mol: 0.03 mol: 60 mL, and the ratio of intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid is 0.01 mol: 5 g: 0.05 g;

[0058] Step B3: Precursor 1, hyperbranched siloxane and N,N-dimethylformamide were mixed and ultrasonically dispersed for 30 minutes, and reacted for 24 hours at a stirring rate of 180 rpm and a temperature of 130°C to obtain precursor 2, 3-mercaptopropyltriethoxysilane and ethanol solution were mixed, and stirred at a stirring rate of 100 rpm and room temperature, and commercially available Taicheng basalt fiber was added and reacted for 3 hours, and then precursor 2 was added and the reaction was continued for 4 hours to obtain composite fibers;

[0059] The amount ratio of precursor 1, hyperbranched siloxane and N,N-dimethylformamide is 1.2g:4g:100mL, the mass fraction of the ethanol solution is 70%, and the amount ratio of 3-mercaptopropyltriethoxysilane, ethanol solution, basalt fiber and precursor 2 is 8g:1000mL:20g:3g.

[0060] Embodiment 3 A production process of an anti-aging and anti-skid asphalt concrete comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 15 parts of commercially available Karamay Grade A matrix asphalt, 30 parts of commercially available Xiang'antong coarse aggregate, 25 parts of commercially available Yanhu fine aggregate, 20-30 parts of commercially available Yandong Haotian steel slag, 4 parts of commercially available Yunxin styrene-butadiene rubber, 8 parts of composite microspheres, 15 parts of composite fibers and 0.8 parts of tetraethoxysilane crosslinking agent;

[0061] Step S2: heating the base asphalt to 180° C., stirring and adding a mixture of coarse aggregate, fine aggregate and steel slag at a stirring rate of 400 rpm, stirring for 3 hours, then adding styrene-butadiene rubber, composite microspheres, composite fibers and a cross-linking agent, and continuing to stir for 3 hours to obtain an anti-aging and anti-skid asphalt concrete;

[0062] The composite microspheres are prepared by the following steps:

[0063] Step A1: mix hexadecyltrimethylammonium bromide, tetrabutyl titanate and anhydrous ethanol, stir and add deionized water at a stirring rate of 300 rpm and room temperature, stir for 3 hours, heat to 120°C, react for 5 hours, centrifuge, dry, grind, and calcine at 500°C for 4 hours to obtain mesoporous titanium oxide, mix commercially available Jixin Yibang asphalt regeneration agent and anhydrous ethanol, stir and add mesoporous titanium oxide at a stirring rate of 450 rpm and a temperature of 100°C, evacuate to 0.1 MPa, and stir for 1 hour to obtain loaded titanium oxide;

[0064] The dosage ratio of hexadecyltrimethylammonium bromide, tetrabutyl titanate, anhydrous ethanol and deionized water is 3g:10g:50mL:10mL, and the dosage ratio of asphalt regeneration agent and mesoporous titanium oxide is 4g:0.8g;

[0065] Step A2: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and dichloromethane were mixed, and triethylamine and bis(trichloromethyl) carbonate were added under stirring at a stirring rate of 150 rpm and room temperature, and the mixture was reacted for 15 min to obtain intermediate 1;

[0066] The ratio of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, triethylamine and bis(trichloromethyl) carbonate is 0.12 mol:0.7 mol:0.18 mol;

[0067] Step A3: The loaded titanium oxide and 1,4-dioxane were mixed and ultrasonically dispersed for 10-15 minutes, and 5-sulfosalicylic acid was added under stirring at a rate of 140 rpm and a temperature of 80°C, and the reaction was continued for 2.5 hours, and then the intermediate 1 was added and the temperature was lowered to 60°C, and the reaction was continued for 3 hours to obtain composite microspheres;

[0068] The ratio of supported titanium oxide, 5-sulfosalicylic acid and intermediate 1 is 0.8 g: 0.4 g: 0.03 mol;

[0069] The composite fiber is prepared by the following steps:

[0070] Step B1: commercially available Xinyuhong graphene oxide, caprolactam and deionized water were mixed, stirred at a stirring rate of 100 rpm and a temperature of 80°C for 15 min, then ultrasonically dispersed for 30 min, stirred and added with magnesium chloride hexahydrate, continued to stir for 2 h, distilled under reduced pressure, then heated to 100°C and added with sodium hydroxide, reacted for 3 h, to obtain precursor 1;

[0071] The amount ratio of graphene oxide, caprolactam, deionized water, magnesium chloride hexahydrate and sodium hydroxide is 0.6g:100g:60mL:3.5g:1.5g;

[0072] Step B2: Tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol were mixed, and the mixture was reacted for 12 hours at a stirring rate of 150 rpm and a temperature of 80° C. to obtain intermediate a; intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid were mixed, and the mixture was reacted for 4 hours at a stirring rate of 80 rpm and a temperature of 140° C. under nitrogen protection to obtain hyperbranched siloxane;

[0073] The ratio of tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol is 0.032 mol: 0.032 mol: 60 mL, and the ratio of intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid is 0.012 mol: 6 g: 0.05 g;

[0074] Step B3: Precursor 1, hyperbranched siloxane and N,N-dimethylformamide were mixed and ultrasonically dispersed for 30 minutes, and reacted for 24 hours at a stirring rate of 180 rpm and a temperature of 130°C to obtain precursor 2, 3-mercaptopropyltriethoxysilane and ethanol solution were mixed, and stirred at a stirring rate of 120 rpm and room temperature, and commercially available Taicheng basalt fiber was added and reacted for 3 hours, and then precursor 2 was added and the reaction was continued for 6 hours to obtain composite fibers;

[0075] The amount ratio of precursor 1, hyperbranched siloxane and N,N-dimethylformamide is 1.4g:4g:100mL, the mass fraction of the ethanol solution is 70%, and the amount ratio of 3-mercaptopropyltriethoxysilane, ethanol solution, basalt fiber and precursor 2 is 10g:1000mL:20g:4g.

[0076] Comparative Example 1 Compared with Example 3, this comparative example removes the asphalt regeneration agent in the preparation process of the composite microspheres in Example 3, and the other steps are the same.

[0077] Comparative Example 2 Compared with Example 3, this comparative example removes the intermediate 1 in the preparation process of the composite microspheres in Example 3, and the other steps are the same.

[0078] Comparative Example 3 Compared with Example 3, this comparative example is characterized in that the precursor 1 in the composite fiber preparation process of Example 3 is replaced by graphene oxide, and the other steps are the same.

[0079] Comparative Example 4 Compared with Example 3, this comparative example is characterized in that the hyperbranched siloxane in the composite fiber preparation process of Example 3 is replaced by hydroxyl-terminated polysiloxane, and the other steps are the same.

[0080] Take the anti-aging and anti-skid asphalt concrete prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, make them into 300mm×300mm×50mm samples, heat age them at a temperature of 160°C for 2h, and then use a pressure heat aging instrument to perform pressure aging for 20h at a temperature of 100°C and an air pressure of 2.1MPa. Perform a rutting test on them for 60min, with a reciprocating rolling speed of 40 times / min. The dynamic stability and cumulative deformation after heat aging are obtained to evaluate their heat aging resistance. The samples are heat aged at a temperature of 160°C for 2h, and then a UV aging instrument is used to perform pressure aging at an UV intensity of 400mW / cm 2 Under the conditions, UV aging was carried out for 20 hours, and then a rutting test was carried out to obtain the dynamic stability and cumulative deformation after UV aging to evaluate its anti-UV aging ability. The pendulum friction coefficient tester was used to measure the swing value of the sample before and after aging, and the swing value retention rate was calculated to evaluate its anti-aging and anti-skid performance. The test results are shown in Table 1:

[0081] Table 1 Test results

[0082]

[0083]

[0084] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 removes the asphalt regeneration agent in the preparation process of the composite microspheres of Example 3. Due to the lack of asphalt regeneration agent, the performance of the asphalt concrete after aging is greatly reduced. Comparative Example 2 removes the intermediate 1 in the preparation process of the composite microspheres of Example 3. Due to the lack of porphyrin structure and isocyanate group, the ultraviolet absorption ability cannot be improved and cross-linking nodes cannot be formed, resulting in a significant decline in its performance after ultraviolet aging, and the performance after thermal aging also decreases to a certain extent. Comparative Example 3 replaces the precursor 1 in the preparation process of the composite fiber of Example 3 with graphene oxide. Due to the lack of magnesium hydroxide, its lamellar structure cannot be formed, and there is a lack of cross-linking nodes, resulting in a decline in its various performances. Comparative Example 4 replaces the hyperbranched siloxane in the preparation process of the composite fiber of Example 3 with hydroxy-terminated polysiloxane. Due to the lack of formation of a cross-linked network, its various performances are greatly reduced.

[0085] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0086] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A production process for anti-aging and anti-skid asphalt concrete, characterized by: The method comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 10-15 parts of matrix asphalt, 25-30 parts of coarse aggregate, 20-25 parts of fine aggregate, 20-30 parts of steel slag, 3-4 parts of styrene-butadiene rubber, 6-8 parts of composite microspheres, 12-15 parts of composite fibers and 0.5-0.8 parts of a cross-linking agent; Step S2: heat the base asphalt to 180°C, stir and add a mixture of coarse aggregate, fine aggregate and steel slag at a stirring rate of 400 rpm, stir for 2-3 hours, then add styrene-butadiene rubber, composite microspheres, composite fibers and a cross-linking agent, and continue stirring for 2-3 hours to obtain an anti-aging and anti-skid asphalt concrete.

2. The production process of the anti-aging and anti-skid asphalt concrete according to claim 1 is characterized by: The composite microspheres are prepared by the following steps: Step A1: mix hexadecyltrimethylammonium bromide, tetrabutyl titanate and anhydrous ethanol, stir and add deionized water at a stirring rate of 250-300rpm and room temperature, stir for 2-3h, heat to 120°C, react for 4-5h, centrifuge, dry, grind, and calcine at 500°C for 4h to obtain mesoporous titanium oxide, mix asphalt regeneration agent and anhydrous ethanol, stir and add mesoporous titanium oxide at a stirring rate of 400-450rpm and a temperature of 100°C, evacuate to 0.1MPa, and stir for 1h to obtain loaded titanium oxide; Step A2: 5,10,15,20-tetrakis(4-aminophenyl)porphyrin and dichloromethane were mixed, and triethylamine and bis(trichloromethyl) carbonate were added under stirring at a rate of 120-150 rpm and room temperature, and the mixture was reacted for 10-15 minutes to obtain intermediate 1; Step A3: Mix the loaded titanium oxide and 1,4-dioxane and disperse them ultrasonically for 10-15 minutes. Stir and add 5-sulfosalicylic acid at a stirring rate of 120-140 rpm and a temperature of 80°C. React for 2-2.5 hours. Then add intermediate 1 and cool to 60°C. Continue to react for 2-3 hours to obtain composite microspheres.

3. The production process of the anti-aging and anti-skid asphalt concrete according to claim 2 is characterized by: In step A1: the usage ratio of hexadecyltrimethylammonium bromide, tetrabutyl titanate, anhydrous ethanol and deionized water is 2.8-3g:8-10g:40-50mL:8-10mL, and the usage ratio of asphalt regeneration agent and mesoporous titanium oxide is 3-4g:0.6-0.8g.

4. The production process of the anti-aging and anti-skid asphalt concrete according to claim 2 is characterized by: In step A2, the ratio of 5,10,15,20-tetrakis(4-aminophenyl)porphyrin, triethylamine and bis(trichloromethyl) carbonate is 0.1-0.12 mol: 0.6-0.7 mol: 0.15-0.18 mol.

5. The production process of the anti-aging and anti-skid asphalt concrete according to claim 2 is characterized by: In step A3: the amount ratio of supported titanium oxide, 5-sulfosalicylic acid and intermediate 1 is 0.6-0.8 g: 0.3-0.4 g: 0.02-0.03 mol.

6. The production process of the anti-aging and anti-skid asphalt concrete according to claim 1 is characterized by: The composite fiber is prepared by the following steps: Step B1: Graphene oxide, caprolactam and deionized water were mixed, stirred at a stirring rate of 80-100 rpm and a temperature of 80° C. for 15 min, then ultrasonically dispersed for 30 min, stirred and magnesium chloride hexahydrate was added, and the stirring was continued for 2 h, and the mixture was distilled under reduced pressure, and then the temperature was raised to 100° C. and sodium hydroxide was added, and the reaction was carried out for 2-3 h to obtain a precursor 1; Step B2: Tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol are mixed, and the mixture is reacted for 12 hours at a stirring rate of 120-150 rpm and a temperature of 80° C. to obtain an intermediate a; the intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid are mixed, and the mixture is reacted for 3-4 hours at a stirring rate of 60-80 rpm and a temperature of 140° C. under nitrogen protection to obtain a hyperbranched siloxane; Step B3: Precursor 1, hyperbranched siloxane and N,N-dimethylformamide are mixed and ultrasonically dispersed for 30 minutes, and reacted for 24 hours at a stirring rate of 150-180 rpm and a temperature of 130°C to obtain precursor 2. 3-Mercaptopropyltriethoxysilane and ethanol solution are mixed, and basalt fiber is added at a stirring rate of 100-120 rpm and room temperature, and reacted for 2-3 hours. Precursor 2 is then added and the reaction is continued for 4-6 hours to obtain a composite fiber.

7. The production process of the anti-aging and anti-skid asphalt concrete according to claim 6 is characterized by: In step B1, the ratio of graphene oxide, caprolactam, deionized water, magnesium chloride hexahydrate and sodium hydroxide is 0.5-0.6 g: 95-100 g: 50-60 mL: 3-3.5 g: 1.2-1.5 g.

8. The production process of the anti-aging and anti-skid asphalt concrete according to claim 6 is characterized by: In step B2, the ratio of tris(hydroxymethyl)aminomethane, maleic anhydride and ethanol is 0.03-0.032 mol: 0.03-0.032 mol: 50-60 mL, and the ratio of intermediate a, hydroxyl-terminated polysiloxane and p-toluenesulfonic acid is 0.01-0.012 mol: 5-6 g: 0.04-0.05 g.

9. The production process of the anti-aging and anti-skid asphalt concrete according to claim 6, characterized in that: In step B3: the amount ratio of precursor 1, hyperbranched siloxane and N,N-dimethylformamide is 1.2-1.4g:3-4g:80-100mL, the mass fraction of the ethanol solution is 70%, and the amount ratio of 3-mercaptopropyltriethoxysilane, ethanol solution, basalt fiber and precursor 2 is 8-10g:1000mL:15-20g:3-4g.

10. A production process for anti-aging and anti-skid asphalt concrete, characterized by: Prepared according to any one of the production processes described in claims 1-9.

Citation Information

Cited By

  • Regenerated asphalt mixture thin layer based on oriented migration of aged asphalt and preparation method thereof

    CN122586437A